2019
DOI: 10.1177/2055116919879256
|View full text |Cite
|
Sign up to set email alerts
|

Feline coronavirus-associated myocarditis in a domestic longhair cat

Abstract: Case summary A 9-month-old entire male domestic longhair indoor cat presented with a 3-week history of fluctuating fever, weight loss and small intestine diarrhoea, which was unresponsive to antibiotics and supportive treatment. Abdominal ultrasound revealed severe jejunal and ileocolic junction intestinal wall thickening with loss of layering. An enterectomy was performed and histopathology revealed severe pyogranulomatous enteritis with vasculitits, compatible with the diagnosis of feline infectious peritoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…Following an enterectomy to remove the affected segments of intestine, histopathology confirmed the presence of severe pyogranulomatous enteritis with vasculitis. 40…”
Section: Gastrointestinal Wall Thickening: Diffuse Vs Focal Thickeningmentioning
confidence: 99%
“…Following an enterectomy to remove the affected segments of intestine, histopathology confirmed the presence of severe pyogranulomatous enteritis with vasculitis. 40…”
Section: Gastrointestinal Wall Thickening: Diffuse Vs Focal Thickeningmentioning
confidence: 99%
“…A study of myocarditis resulted from feline coronavirus has been published recently. Bilateral atrial expansion and left ventricular hypertrophy have been observed in the cat, which might further cause heart failure [ 38 ].…”
Section: Cardiac Disorders Are Presented During Various Covs Infectiomentioning
confidence: 99%
“…Myocarditis is an inflammatory disease of the myocardium, diagnosed by established histological, immunological and immune-histochemical criteria, caused by infectious, immune-mediated or toxic agents [40]. A previous case report described coronavirus-associated myocarditis in animal models [41], as well as in humans during MERS-CoV infection [42].…”
Section: Myocarditismentioning
confidence: 99%